2007
DOI: 10.1186/1742-4690-4-73
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spread of mouse mammary tumor virus in cultured human breast cells

Abstract: Taken together, our results show that human cells can support replication of mouse mammary tumor virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 23 publications
3
62
0
Order By: Relevance
“…Our current observations in DCIS and IDC breast cancer specimens validate the previous experimental evidence that MMTV can infect, multiply, and randomly integrate into the DNA of normal human breast epithelial cells (8)(9)(10). Together, these data suggest a possible causal role for MMTV-like virus in some human breast cancers.…”
Section: Interpretation Of the Datasupporting
confidence: 87%
See 1 more Smart Citation
“…Our current observations in DCIS and IDC breast cancer specimens validate the previous experimental evidence that MMTV can infect, multiply, and randomly integrate into the DNA of normal human breast epithelial cells (8)(9)(10). Together, these data suggest a possible causal role for MMTV-like virus in some human breast cancers.…”
Section: Interpretation Of the Datasupporting
confidence: 87%
“…In a recent study, env and long terminal repeat sequences with >98% homology to those of MMTV have been identified in breast cancers that had occurred in a mother, father, and daughter of the same family, living under the same roof (7). MMTV can infect, integrate, and multiply in human breast epithelial cancer cell lines (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that XMRV infectivity can be limited by the presence of known host restriction factors to retroviral replication, such as the human APOBEC3 and tetherin proteins, as well as mouse APOBEC3, tetherin, and Fv1 proteins (11,28). It is noteworthy that a number of human cells, including breast cells have been shown to be susceptible to infection by the mouse mammary tumor virus (MMTV) (13,14), in spite of the fact that the human orthologue of the murine transferrin receptor 1 (Trf1), which is the known cellular receptor for MMTV, is not able to support viral entry in human cells (32). In a recent study, XMRV protein antigens have been detected mainly in malignant prostatic epithelial cells (23%) but only rarely in stromal cells (4%) of prostate cancer tissues collected from one institution (34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has recently been reported (9) that inflammatory breast cancers from American women show a higher incidence of HMTV-related viral sequences (71%) than sporadic breast cancers, and that the presence of MMTV-env-like exogenous sequences is strictly related to tumor progression (10). Additional support for possible involvement of the virus in breast cancer comes from reports claiming that MMTV can infect and spread through a culture of human mammary cells (11,12); the MMTV env protein, through a specific sequence motif, can initiate changes that are consistent with transformation of mammary epithelial cells (13); cells isolated from ascites or pleural effusions of patients with metastatic breast cancer contained MMTV sequences in their DNA, expressed the MMTV Env protein and showed b-retroviral particles by electron microscopy, similar to the mouse virus (14). The same group recently reported detection of HMTV proteins in human breast cancer cells (15).…”
Section: Introductionmentioning
confidence: 99%